Temnospondyl diversity of the Permian-Triassic Colonia Orozco Local Fauna (Buena Vista Formation) of Uruguay - Piñeiro, Graciela (2007)
Temnospondyls are the most abundant constituent of the Colonia Orozco Local Fauna of the Uruguayan Buena Vista Formation (Paraná Basin), contrasting with that observed at most latest Permian and earliest Triassic assemblages elsewhere. The components of the Colonia Orozco fauna, appear to represent early stages of the turnover evidenced in the communities of continental tetrapods at the Permo-Triassic boundary. They include plesiomorphic representatives of groups present in Early Triassic assemblages as well as relicts of Late Permian taxa. In particular, the presence of a close relative of the Russian dvinosauroid, Dvinosaurus, implies a dispersal event of this taxon to Gondwana probably during the Late Permian. Comparisons of the Colonia Orozco fauna to other Permo-Triassic communities indicate that it could be older than the Brazilian Lower Triassic Catuçaba Local Fauna of the Sanga do Cabral Formation (Paraná Basin) and probably equivalent to the latest Permian Russian Vyazniki Community. Moreover, the Colonia Orozco fauna could be close to the assemblages represented in the lowermost portion of the South African Lower Triassic Lystrosaurus Assemblage Zone and probably to the Arcadia Formation of Australia.